Patton [videorecording (DVD)] - Schaffner, Franklin J.; Scott, George C., 1927-1999; Malden, Karl; Bates, Michael, 1920-1978; Farago, Ladislas; Bradley, Omar Nelson, 1893-1981 (Twentieth Century Fox Home Entertainment, 2006)
A dramatization of the experiences of General George S. Patton during World War II.